(untitled) (LEARNing Landscapes, 2010)
Within current Canadian learning environments, learners bring sophistication in areas such as communication/technology, a wide diversity of learning needs, and often an orientation towards social justice. This commentary refers to the ongoing responsiveness of teacher education programs to these evolving learner attributes, using as exemplars the areas of global citizenship education and technology integration. A backdrop for this discussion is the observation that the knowledge and skills that contribute to successful adult lives are also evolving.